Syndrome of inappropriate antidiuretic hormone secretion associated with seronegative neuromyelitis optica spectrum disorder - Shin Ju Oh; Chun Gyoo Ihm; Tae Won Lee; Jin Sug Kim; Da Rae Kim; Eun Ji Park; Su Woong Jung; Ji-Hoon Lee; Sung Hyuk Heo; Kyung Hwan Jeong (The Korean Society of Nephrology, 2017)
The syndrome of inappropriate antidiuretic hormone secretion (SIADH) is a potential cause of hyponatremia of the central nervous system (CNS). Although SIADH has been reported to be associated with many other central nervous disorders, its association with neuromyelitis optica (NMO) or NMO spectrum disorders are rare. NMO is a demyelinating disorder characterized by optic neuritis and transverse myelitis. Aquaporin-4 (AQP4), which is the target antigen for a NMO autoantibody, is the predominant CNS water channel. However, some NMO patients show seronegative AQP4 antibody results. The spectrum of NMO has been changed, and new findings about the disease have been reported. Here, we report a case of seronegative NMO spectrum disorder associated with SIADH.